2020
DOI: 10.1038/s41398-020-01002-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of choline treatment on behavioral and neurochemical autistic-like phenotype in Mthfr-deficient mice

Abstract: Imbalanced one carbon metabolism and aberrant autophagy is robustly reported in patients with autism. Polymorphism in the gene methylenetetrahydrofolate reductase (Mthfr), encoding for a key enzyme in this pathway is associated with an increased risk for autistic-spectrum-disorders (ASDs). Autistic-like core and associated behaviors have been described, with contribution of both maternal and offspring Mthfr+/− genotype to the different domains of behavior. Preconception and prenatal supplementation with methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 98 publications
(141 reference statements)
1
30
0
Order By: Relevance
“…Previous work in our labs showed that gestational exposure to the pesticide chlorpyrifos (C 9 H 11 C l3 NO 3 PS, CID2730, CPF) ( Lan et al, 2017 , 2019 ) and the Mthfr heterozygosity (Mthfr+/−) in mice ( Sadigurschi and Golan, 2018 ; Orenbuch et al, 2019 ; Agam et al, 2020 ) are both associated with impaired social preference and restricted or repetitive behavior, establishing them as mouse models of ASD with face validity. Mouse pups in both models present with developmental delay, in agreement with a neurodevelopmental delay observed in part of ASD patients ( Furlong et al, 2014 ; Shelton et al, 2014 ).…”
Section: Introductionmentioning
confidence: 91%
“…Previous work in our labs showed that gestational exposure to the pesticide chlorpyrifos (C 9 H 11 C l3 NO 3 PS, CID2730, CPF) ( Lan et al, 2017 , 2019 ) and the Mthfr heterozygosity (Mthfr+/−) in mice ( Sadigurschi and Golan, 2018 ; Orenbuch et al, 2019 ; Agam et al, 2020 ) are both associated with impaired social preference and restricted or repetitive behavior, establishing them as mouse models of ASD with face validity. Mouse pups in both models present with developmental delay, in agreement with a neurodevelopmental delay observed in part of ASD patients ( Furlong et al, 2014 ; Shelton et al, 2014 ).…”
Section: Introductionmentioning
confidence: 91%
“…SAM formation is dependent on the levels of cellular micronutrients that play a role in these cycles, such as folate, methionine, betaine, choline, VitB2, VitB6 and VitB12 [ 12 , 13 ] ( Figure 1 ). These micronutrients can be derived from the diet, indicating that the quality of our diet across the lifespan will influence the one-carbon cycle and influence general health, including mental health [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Nutrients Genes and The Epigenomementioning
confidence: 99%
“…Furthermore, MTHFR polymorphism was associated with an increased risk of ASD, and the offspring of Mthfr + / − mice ( Pu et al, 2013 ), whether wild-type or heterozygous, exhibited autism-like behaviors. It is surprising that after 14 days of choline supplementation, the characteristics of RRBs were offset ( Agam et al, 2020 ). In addition, other supplementary treatments showed promising effects in ASD animals.…”
Section: Treatment and Intervention Of Repetitive Restricted Behaviorsmentioning
confidence: 99%